Decellularized homograft for aortic valve replacement two years after lung transplantation - P. Iablonskii; F. Ius; I. Tudorache; A. Martens; S. Sarikouch; J. Salman; A. Haverich; S. Cebotari (Вестник трансплантологии и искусственных органов)
Cardiac valvular surgery in patients after lung transplantation is a challenging procedure, reports are scarce. We report a 29-year-old patient who underwent concomitant mitral valve reconstruction and implantation of a decellularized aortic homograft two years after bilateral lung transplantation.